Students’ Satisfaction Level of English Online Learning at SMPN 1 Ampek Angkek - Oktaviani, Resi (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2022)
This research was conducted because the researcher found several problems, namely: Some students difficult to understand the material, Limited internet network access, and Most students are looked less enthusiastic about learning online. This study aims to see the students' satisfaction level of English online learning.This type of research is survey research. The population and sample of this study were class VIII SMP N 1 ampek angkek. Where this research uses the incidental technique. The data collection technique is through a questionnaire or questionnaire as an instrument. The data analysis technique is collecting data, tabulate the data, calculate the data to average, and interpret the data. Based on the results of research and data analysis, the research found that students satisfaction in implementing online learning on the learning technologies item, the results showed that the students were quite satisfied with the learning carried out, namely the data obtained (64,92%). Students' satisfaction in the item pedagogical models shows that students were quite satisfied with the data obtained (71,51%). And students' satisfaction in online learning with the instructional strategy item shows the results that students are quite satisfied with the data obtained (64,08%). Based on the results of this study it can be concluded that the students in class eight at SMP N 1 Ampek Angkek are quite satisfied with English online learning that has been done by obtaining 66,83% data which means quite satisfied.